Upregulated Interleukin 21 Receptor Enhances Proliferation and Epithelial-Mesenchymal Transition Process in Benign Prostatic Hyperplasia - Xu, Deqiang; Chen, Ping; Xiao, He; Wang, Xinghuan; DiSanto, Michael E.; Zhang, Xinhua (Frontiers in Endocrinology, 2019)
Background: Interleukins (ILs) and related chronic inflammation have been found to contribute to the development of benign prostatic hyperplasia (BPH) in recent decades. As a late member of the ILs family, IL-21 receptor (IL-21R) can modulate cell proliferation, however, IL-21R activity in the prostate has not been examined. The current study aimed to elucidate a potential role of IL-21R in the development of BPH. Material and Methods: Human prostate tissues, cell lines and rats were used. QRT-PCR, Western blot, and immunohistochemistry, along with hematoxylin and eosin, Masson's trichrome, and immunofluorescent staining were performed. BPH-1 cells with IL-21R silenced were cultured or co-cultured with macrophages (active THP-1, AcTHP-1). Apoptosis and cell cycle phases were determined via flow cytometry. Epithelial-mesenchymal transition (EMT) processes were also examined. In vivo, rat prostatitis was induced with intraprostatic injected lipopolysaccharide (LPS). Results: IL-21R was highly expressed in human as well as rat prostate, mainly in the epithelial compartment. BPH concomitant with prostatitis significantly upregulated the expression of IL-21R. Knockdown of IL-21R induced cell apoptosis and cycle arrest at G0/G1 phase, and blocked the EMT process in BPH-1 cells. When IL-21R silenced BPH-1 cells were co-cultured with AcTHP-1 cells, these aforementioned processes and IL-21R change were completely reversed. Prostatic hyperplasia was observed with IL-21R upregulated in LPS induced prostatitis rats. More specifically, the expression of apoptosis, cyclin, and EMT proteins in this rat model are altered in a manner consistent with that seen in the cell line model. Conclusions: Our novel data demonstrates the expression and functional activities of IL-21R in the mechanism for development of BPH. IL-21R mainly localized in prostate epithelium and it was upregulated in hyperplastic prostate tissues. IL-21R enhanced proliferation of BPH-1 cells, via inhibiting cell apoptosis, and modulating cell cycles, as well as the EMT process, in response to inflammatory stimuli.